O imaginário de Caxias do Sul nas crônicas publicadas em jornais locais, entre 1900 e 1930 - Cechinato, Natalia Susin (My University, 2019)
This dissertation investigates the representation of the urban imaginary in the chronicles published in newspapers of Caxias do Sul, between 1900-1930. Through the gathering and selection of unpublished chronicles on research, which are available in the digital collection of the Câmara Municipal de Vereadores, we observe aspects related to the urban and cultural development of the city. For this, the set of chronicles will be analyzed from four axes of analysis: 1. The train; 2. The square; 3. The street; and 4. The cinema. The research takes as theoretical and critical support the discussions of Marshall Berman (2007) and Beatriz Sarlo (2010) on modernity, Castoriadis (2000) and Pesavento (1999), about the imaginary of the city.
Esta dissertação investiga a representação do imaginário urbano nas crônicas publicadas em jornais de Caxias do Sul, entre 1900 e 1930. Por meio da coleta e seleção de crônicas inéditas em pesquisa, que estão disponíveis no acervo digital da Câmara Municipal de Vereadores, observam-se aspectos relacionados ao desenvolvimento urbano e cultural da cidade. Para tanto, o conjunto de crônicas será analisado a partir de quatro eixos: 1. O trem; 2. A praça; 3. A rua; e 4. O cinema. A pesquisa toma como suporte teórico e crítico as discussões de Berman (2007) e Sarlo (2010) sobre a modernidade, Castoriadis (2000) e Pesavento (1999) sobre o imaginário da cidade.
Keywords: Crônicas - Crítica e interpretação; Jornais - Caxias do Sul (RS); Memória coletiva; Chronicles - Criticism and interpretation; Newspapers -Caxias do Sul(Brazil); Collective memory